P622 Comparison of midterm outcomes in Pediatric Crohn's Disease patients treated with either Exclusive Enteral Nutrition or Corticosteroids around disease diagnosis– a population based study. (27th May 2021) - Plotkin, L; Focht, G; Harel, S; Dotan, I; Greenfeld, S; Kariv, R; Gabay, H; Loewenberg Weisband, Y; Turner, D
Abstract: Background: Corticosteroids (CS) and exclusive enteral nutrition (EEN) are commonly used as induction therapy in pediatric Crohn's disease (PCD). Pediatric studies showed that CS treatment is equivalent to EEN for induction of remission, and it is easier to tolerate. However, EEN may be associated with superior long-term outcomes but this remains controversial. We thus aimed in this population-based study to compare CS dependency rate in children receiving EEN vs CS as induction therapy at the time of diagnosis, and to explore additional outcomes after one and two years of follow-up: IBD-related surgery, hospitalizations, and the use of biologics. Methods: This study was performed on data from two Israeli Health Maintenance Organizations (HMOs), covering 78% of the population. We included all PCD patients (<18 years) diagnosed between 2005 and 2017 treated with EEN or CS within the first six months of diagnosis, with at least one-year follow-up. We excluded patients who initiated biologics within the same quarter. CS dependency was defined as a systemic steroid course lasting >90 days or four purchases with 12 months. Results: A total of 2, 730 PCD were identified, of whom 669 (24.5%) received induction therapy with either EEN [n=227 (8.3%)] or CS ([n=442 (16.2%)]. Median age at diagnosis was 13.04 years (3.8). Baseline (BL) characteristics, including age at diagnosis, anthropometrics data and gender, were similar between the groups. Steroid dependency was higher in the CS group compared to the EEN group during the 1 st and the 2 nd year (10% vs. 7%, p<0.001 and 14% vs. 12%, p<0.001 respectively). Use of biologics was higher in the 1 st but not the 2 nd year in the EEN group compared to the CS group (28% vs. 19%, p=0.0016 and 40% vs. 33%, p=0.066 respectively). Hospitalization rate was higher in the CS group in both the 1 st and 2 nd years (42% vs. 22%, p<0.001 and 51% vs. 30%, p<0.001 respectively). There were no differences between the groups in surgeries rate and growth during the 1 st and 2 nd year follow-ups. Conclusion: The use of CS as induction therapy in PCD was associated with a higher corticosteroid dependency rate, as well as more hospitalizations during the first two years of follow-up.